Investigation of aqueous soluble proanthocyanidins in the inflorescence of Cocos nucifera L. - Padumadasa, C.; Dharmadana, D.; Abeysekera, A.M.; Thammitiyagodage, M.G. (Journal of Pharmacognosy and Phytochemistry, 2016)
Attached

Proanthocyanidins belong to a class of polyphenolic compounds called flavonoids and they have been reported to exhibit important pharmacological activities. We have previously reported the extraction, purification and characterization of the ethyl acetate soluble proanthocyanidins (EASPA) of the inflorescence of Cocos nucifera L. The aqueous soluble proanthocyanidins (AQSPA) were extracted from the immature inflorescence using acetone/water (7:3) and purified using chromatography on sephadex LH-20. Acid catalyzed cleavage studies and thiolytic studies were carried out to determine the monomeric composition of AQSPA. In addition, AQSPA was subjected to 13C NMR spectroscopy to study the occurrence of proanthocyanidins in this fraction. The AQSPA fraction of an acetone/water (7:3) extract of Cocos nucifera L. inflorescence was purified by chromatography on Sephadex LH-20 to yield purified AQSPA as an off white powder in 1.17% on dry weight basis. Acid catalyzed cleavage followed by TLC analysis indicated that AQSPA is composed of (epi)catechin and (epi)afzelechin monomeric units while thiolysis followed by NMR spectroscopy revealed the monomers to be the epiisomers. 13C NMR studies of AQSPA showed signals characteristic for epicatechin units indicating that AQSPA is composed mainly of epicatechin units with few of epiafzelechin units as previously reported for EASPA. However, AQSPA is comprised of high molecular weight proanthocyanidins and the oligomeric profile is different to that of EASPA.
Keywords: Cocos nucifera inflorescence; proanthocyanidin; epicatechin; epiafzelechin; thiolysis